Revitalized Karuk and Yurok cultural burning to enhance California hazelnut for basketweaving in northwestern California, USA - Marks-Block, Tony; Lake, Frank K.; Bliege Bird, Rebecca; Curran, Lisa M. (Fire ecology, 2021)
Background Karuk and Yurok tribes in northwestern California, USA, are revitalizing the practice of cultural burning, which is the use of prescribed burns to enhance culturally important species. These cultural burns are critical to the livelihoods of indigenous peoples, and were widespread prior to the establishment of fire exclusion policies. One of the major objectives of cultural burning is to enhance California hazelnut ( Corylus cornuta Marsh var. californica ) basketry stem production for Karuk and Yurok basketweavers. To evaluate cultural burning as a form of human ecosystem engineering, we monitored hazelnut basketry stem production, qualities, and shrub density in 48 plots (400 m 2 ) within two prescribed and 19 cultural burn sites. Socio-ecological variables that were analyzed included burn frequency, burn season, overstory tree (≥10 cm diameter at breast height) basal area, ungulate browse, and aspect. We also observed basketry stem gathering to compare travel distances, gathering rates, and basketweaver preferences across sites with different fire histories and land tenure. Results Hazelnut shrubs, one growing season post burn, produced a 13-fold increase in basketry stems compared with shrubs growing at least three seasons post burn ( P < 0.0001). Basketry stem production and stem length displayed negative relationships with overstory tree basal area ( P < 0.01) and ungulate browse ( P < 0.0001). Plots burned at high frequency (at least three burn events from 1989 to 2019) had 1.86-fold greater hazelnut shrubs than plots experiencing less than three burn events ( P < 0.0001), and were all located on the Yurok Reservation where land tenure of indigenous people is comparatively stronger. Basketweavers travelled 3.8-fold greater distance to reach gathering sites burned by wildfires compared with those that were culturally burned ( P < 0.01). At cultural burn sites, wildfire sites, and fire-excluded sites, mean gathering rates were 4.9, 1.6, and 0.5 stems per minute per individual, respectively. Conclusions Karuk and Yurok cultural fire regimes with high burn frequencies ( e.g., three to five years) promote high densities of hazelnut shrubs and increase hazelnut basketry stem production. This improves gathering efficiency and lowers travel costs to support the revitalization of a vital cultural practice. Our findings provide evidence of positive human ecosystem engineering, and show that increasing tribal sovereignty over fire management improves socio-economic well-being while at the same time supports measures of ecosystem structure and function.